Suddenly developed haemorrhagic olecranon bursitis is related to traumatic asymptomatic heterotopic ossification - Unlu, Zeliha; Selim Tokmak, Yavuz; Sahillioglu, Ali (Annals of Medical Research, 2021)
None
Keywords: None